Green budgeting and sustainable development: Fiscal efficiency as a transmission mechanism - Suroso, Sugeng; Mala, Chajar Matari Fath; Jumono, Sapto (The Economics and Finance Letters, 2026)
The Sustainable Development Goals (SDGs) constitute an indivisible agenda for achieving economic development, environmental sustainability, and social inclusion. Green budgeting, in which sustainability considerations are incorporated into public investment allocations, has emerged as a key fiscal tool to advance this agenda. This article investigates the evolving link among green budgeting, fiscal efficiency, and sustainable development performance using Indonesian local governments as a case study. Based on district and city panel data for the years 2018 to 2022, and adopting the Structural Equation Modeling–Partial Least Squares (SEM-PLS) mediated analysis technique, our results suggest that green budgeting and fiscal efficiency positively and significantly influence SD outputs. The measurement constructs are demonstrated to be statistically valid and reliable. The findings also suggest that fiscal effectiveness mediates the linkages between green budgeting and development performance. The estimated impact of green budgeting on sustainable development amounts to 0.585, indicating that greener expenditure is associated with lower poverty-alleviation costs (HD index) and better ecosystem conditions. Despite Java being the most developed part of Indonesia, the analysis reveals ongoing structural weaknesses that signify continued spatial imbalances in development outcomes. These have implications for the introduction of green budgeting as an integrated fiscal framework at local and regional levels to mitigate regional disparities and enhance policy performance. Our study helps assess sustainability-oriented public finance actions in central and local governments, as well as provides policy guidance on integrating green budget performance assessment, technical guidance, performance indicators, and incentive systems based on financial efficiency.